1999
DOI: 10.1029/1999jc900112
|View full text |Cite
|
Sign up to set email alerts
|

A simple model for interannual sandbar behavior

Abstract: Abstract. Time and length scales of beach variability have been quantified using 16 years of beach surveys sampled at the Army Corps of Engineers' Field Research Facility, located on the U.S. Atlantic coast. Between 50% and 90% of the bathymetric variability at this site was explained by alongshore-uniform response over the approximately 1 km alongshore span of the surveys. Although the incident wave height variance was dominated by frequencies at or higher than 1 cycle/yr, more than 80% of the bathymetric var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
193
0
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 204 publications
(208 citation statements)
references
References 25 publications
13
193
0
2
Order By: Relevance
“…To reduce the number of inputs for the models, these variables are combined into the wave height at breaking (Plant et al, 1999):…”
Section: Observationsmentioning
confidence: 99%
See 2 more Smart Citations
“…To reduce the number of inputs for the models, these variables are combined into the wave height at breaking (Plant et al, 1999):…”
Section: Observationsmentioning
confidence: 99%
“…Existing analyses of time-series of cross-shore sandbar position have suggested a nonlinear dependence of sandbar migration on various environmental factors, such as the height of the incident waves at breaking, see, for instance, Plant et al (1999). Furthermore, 'memory' is sometimes suggested to be present in time-series of sandbar position, meaning dependencies in sandbar position spanning longer time periods which might even exceed the duration of individual storms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Part of the difficulty is that the relevant scales span a very broad range, from millimeters (individual sand grains) to kilometers (the cross-shore width of the surfzone) and tens of kilometers (alongshore extent of littoral cells). The largest spatial scales are particularly important because they contain the majority of the spatial and temporal variability of nearshore bathymetric change [Lippmann and Holman, 1990;Plant et al, 1999]. These are also the spatial and temporal scales that characterize human interactions with the coast.…”
Section: Introductionmentioning
confidence: 99%
“…As seen in Figure 2 of the revised manuscript, alongshore volume differences between northerly and southerly profiles occur, particularly post 1991. Reversed migration directions of the nearshore sand bars on either side of the FRF pier (Plant et al, 1999), longshore rhythmic sand bars and sand waves (Lippmann and Holman, 1990;Plant and Holman, 1996; Miller and Dean, 2007a,b), and extended periods of shore-oblique waves generating unidirectional longshore sediment transport (Miller et al, 1983; Keen et al, 2003) have been observed to contribute to the alongshore variability at Duck. Furthermore, as the beach profile data used in the present study extend beyond the average position of the depth of closure, gains/losses in beach volume (Figure 2) are expected to be predominantly influenced by longshore processes as cross-shore processes would mainly influence the redistribution of sediment within the profile.…”
Section: C3 "Applying Eq(6) and A Straight And Parallel Coastline Imentioning
confidence: 99%